การเตรียมแผ่นกรองซิลิกาจากขี้เถ้าแกลบ : รายงานผลการวิจัย - สรินทร ลิ่มปนาท (สถาบันวิจัยโลหะและวัสดุ จุฬาลงกรณ์มหาวิทยาลัย, 2000)
To investigate the process of silica filter production from domestic rice husk ash. As a preliminary raw material, the ash was chemically synthesized and then spray dried to produce silica powder with a specific density of 2.098 g/cm3 and a purity of 99.8%. The formation of filters was achieved by using a gel casting process accompanying acrylamide polymerization, in which ratios of initiator, catalyst and silica contents were varied. In this study, it was found that the best ratio of those is 1% initiator, 3.8ml/L catalyst and 50% Vol. Silica, leading to the gellation time of 30 minutes. After sintering at different temperatures and times, samples without cracking are acquired when sintered at 1300oC for an hour.